Exploring and Expanding the Category of ‘Young Workers’ According to Situated Ways of Doing Risk and Safety—a Case Study in the Retail Industry - Nielsen, Mette Lykke; Dyreborg, Johnny; Kines, Pete; Nielsen, Kent J.; Rasmussen, Kurt (Nordic Journal of Working Life Studies, 2013)
Young adult workers aged 18–24 years have the highest risk of accidents at work. Following the work of Bourdieu and Tannock, we demonstrate that young adult workers are a highly differentiated group. Accordingly, safety prevention among young adult workers needs to be nuanced in ways that take into consideration the different positions and conditions under which young adult workers are employed. Based on single and group interviews with 26 young adult workers from six various sized supermarkets, we categorize young adult retail workers into the following five distinct groups: ‘Skilled workers,’ ‘Apprentices,’ ‘Sabbatical year workers,’ ‘Student workers,’ and ‘School dropouts.’ We argue that exposure to accidental risk is not equally distributed among them and offer an insight into the narratives of young adult workers on the subject of risk situations at work. The categorizations are explored and expanded according to the situated ways of ‘doing’ risk and safety in the working practices of the adult workers. We suggest that the understanding of ‘young’ as an age-related biological category might explain why approaches to prevent accidents among young employees first and foremost include individual factors like advice, information, and supervision and to a lesser degree the structural and cultural environment wherein they are embedded. We conclude that age cannot stand alone as the only factor in safety prevention directed at workers aged 18–24 years; if we do so, there is a risk of overemphasizing age-related individual characteristics such as awareness and cognitive limitations before structural, relational, and hierarchical dimensions at the workplace.